Predictive performance of three practical approaches for grapefruit juice‐induced 2‐fold or greater increases in AUC of concomitantly administered drugs. (4th November 2014) - Takahashi, M.; Onozawa, S.; Ogawa, R.; Uesawa, Y.; Echizen, H.
Summary What is known and objective Clinical pharmacists have a challenging task when answering patients' question about whether they can take specific drugs with grapefruit juice (GFJ) without risk of drug interaction. To identify the most practicable method for predicting clinically relevant changes in plasma concentrations of orally administered drugs caused by the ingestion of GFJ, we compared the predictive performance of three methods using data obtained from the literature. Methods We undertook a systematic search of drug interactions associated with GFJ using MEDLINE and the Metabolism & Transport Drug Interaction Database (DIDB version 4.0). We considered an elevation of the area under the plasma concentration‒time curve (AUC) of 2 or greater relative to the control value [AUC ratio (AUCR) ≥ 2·0] as a clinically significant interaction. Results and discussion The data from 74 drugs (194 data sets) were analysed. When the reported information of CYP3A involvement in the metabolism of a drug of interest was adopted as a predictive criterion for GFJ‒drug interaction, the performance assessed by positive predictive value (PPV) was low (0·26), but that assessed by negative predictive value (NPV) and sensitivity was high (1·00 for both). When the reported oral bioavailability of ≤0·1 was used as a criterion, the PPV improved to 0·50 with an acceptable NPV of 0·81, but sensitivity was reduced to 0·21. When the reported AUCR was ≥10 after co‐administration of a typical CYP3A inhibitor, the corresponding values were 0·64, 0·79 and 0·19, respectively. What is new and conclusion We consider that an oral bioavailability of ≤0·1 or an AUCR of ≥10 caused by a CYP3A inhibitor of a drug of interest may be a practical prediction criterion for avoiding significant interactions with GFJ. Information about the involvement of CYP3A in their metabolism should also be taken into account for drugs with narrow therapeutic ranges.